Towards the development of a network library system for Philippine Public administration school libraries - Alfiler, Ana Grace P.; Aguirre, Vyva Victoria M.; David, Lourdes T.; Patacsil, Perla C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
This study evaluates the technological capabilities of libraries offering Public administration in Metro Manila area to initiate and sustain a library network. It aims to bring together the local collections in the field of public administration, to simplify searching through available resources. It focused on the libraries of member schools of the Association of Schools of Public Administration in the Philippines (ASPAP). Fourteen of the seventeen school members located in Metro Manila agreed to participate in the study. A four-page questionnaire was distributed to the head/chief librarians of the participating libraries. The questionnaire focused on the library's level of digitalization, availability of computer equipment, personnel, level of professional training and size and nature of the collection in the field of public administration. Follow-up interviews were done to probe certain responses. The study revealed that among librarians of ASPAP schools in Metro Manila only five librarians were aware of the association and its activities.
There is an abundant collection of materials among the respondents, for both print and non-print materials. Most of the libraries have adequate personnel and available facilities for students, faculty members and library staff members. Although not all libraries have the same level of automation, twelve libraries have adopted Integrated Library System modules that enable their catalogs to be more accessible. However, only six of the fourteen libraries were found to be well equipped and prepared to contribute to the proposed network, based on the library's level of digitization, availability of hardware, personnel training and collection. Given the available resources among respondent libraries, the study concludes that establishing a library network among six of the fourteen libraries is feasible, with the Association of Schools of Public Administration in the Philippines as the central node and the six well equipped schools as the initial contributing members of the network. The establishment of this network of libraries will promote research in public administration as it will enhance access of students, faculty members, researchers and public administration practitioners of the library collection of these schools in Metro Manila. "
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Integrated library systems (Computer systems).; Library information networks -- Philippines -- Manila Metropolitan Area; School libraries -- Philippines -- Mania Metropolitan Area -- Automation